1992
DOI: 10.2307/1964229
|View full text |Cite
|
Sign up to set email alerts
|

Covenants with and without a Sword: Self-Governance Is Possible

Abstract: Contemporary political theory often assumes that individuals cannot make credible commitments where substantial temptations exist to break them unless such commitments are enforced by an external agent. One such situation may occur in relation to common pool resources, which are natural or man-made resources whose yield is subtractable and whose exclusion is nontrivial (but not necessarily impossible). Examples include fisheries, forests, grazing ranges, irrigation systems, and groundwater basins. Empirical ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

49
1,183
7
20

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,710 publications
(1,259 citation statements)
references
References 35 publications
49
1,183
7
20
Order By: Relevance
“…This assumption has been shown to be invalid in a large number of experiments in which participants in social dilemmas have been given the option to contribute to the punishment of others at a cost to themselves; a robust finding is that a substantial proportion of participants voluntarily do so (e.g., Fehr & Gächter 2002;Ostrom, Walker & Gardner 1992;Yamagishi 1986). Thus, it seems that no enforcement is needed for a substantial proportion of people to be willing to engage in punishment of others.…”
Section: Reasons For and Against Prescriptive Rulesmentioning
confidence: 99%
“…This assumption has been shown to be invalid in a large number of experiments in which participants in social dilemmas have been given the option to contribute to the punishment of others at a cost to themselves; a robust finding is that a substantial proportion of participants voluntarily do so (e.g., Fehr & Gächter 2002;Ostrom, Walker & Gardner 1992;Yamagishi 1986). Thus, it seems that no enforcement is needed for a substantial proportion of people to be willing to engage in punishment of others.…”
Section: Reasons For and Against Prescriptive Rulesmentioning
confidence: 99%
“…Ostrom et al (1992) showed the existence of punishment opportunities in a common-pool resource use game. The fear of punishment has a positive effect on cooperation.…”
Section: Do Itqs Provide Adequate Incentives For the Sustainability Omentioning
confidence: 99%
“…All sanctioning experiments used the 25-token design since appropriations had been much higher in this design (Ostrom, Walker, and Gardner, 1992). Subjects played ten rounds of the baseline game modified so that the individual contributions in each round were reported as well as the total outcomes.…”
Section: The First Set Of Sanctioning Experimentsmentioning
confidence: 99%
“…In this set of experiments, subjects were able to increase their returns from the CPR modestly to 39 percent of maximum, but when the costs of fees and fines were subtracted from the total, these gains are wiped out. When subjects were given a single opportunity to communicate prior to the implementation of sanctioning capabilities, they were able to gain an average of 85 percent of the maximum payoffs (69 percent when the costs of the fees and fines were subtracted) (see Ostrom, Walker, and Gardner, 1992;Ostrom, Gardner, and Walker, 1994).…”
Section: The First Set Of Sanctioning Experimentsmentioning
confidence: 99%
See 1 more Smart Citation